Multisensory representation of limb position in human premotor cortex. - Lloyd, D; Shore, D; Spence, C; Calvert, G (2003)
Using functional magnetic resonance imaging (fMRI) in humans, we identified regions of cortex involved in the encoding of limb position. Tactile stimulation of the right hand, across the body midline, activated the right parietal cortex when the eyes were closed; activation shifted to a left parietofrontal network when the eyes were open. These data reveal important similarities between human and non-human primates in the network of brain areas involved in the multisensory representation of limb position.